Inhibition of macrophage activation by the myxoma virus M141 protein (vCD200). - Zhang, L; Stanford, M; Liu, J; Barrett, C; Jiang, L; Barclay, N; McFadden, G (2009)
The M141 protein of myxoma virus (MYXV) is a viral CD200 homolog (also called vOX-2) that inhibits macrophage activation in infected rabbits. Here, we show that murine myeloid RAW 264.7 cells became activated when infected with MYXV in which the M141 gene was deleted (vMyx-M141KO) but not with the parental wild-type MYXV. Moreover, transcript and protein levels of tumor necrosis factor and granulocyte colony-stimulating factor were rapidly upregulated in an NF-kappaB-dependent fashion in the RAW 264.7 cells infected with vMyx-M141KO. M141 protein is present in the virion and counteracts this NF-kappaB activation pathway upon infection with the wild-type MYXV. Our data suggest that upregulation of these classic macrophage-related proinflammatory cytokine markers following infection of myeloid cells with the M141-knockout MYXV is mediated via the rapid activation of the cellular NF-kappaB pathway.